User-tailored climate services for the Andean region - Federal Office of Meteorology and Climatology MeteoSwiss (2016)
Climate services are key to increase climate resilience of vulnerable populations. MeteoSwiss and SENAMHI initiated the Climandes project under the umbrella of the WMO-led Global Framework for Climate Services. Climandes provides high quality climate services and establishes a user-dialog to meet the specific needs of Andean smallholder farmers. Ultimately, this initiative offers a pilot example on how such services can benefit climate-sensitive sectors and, hence, society at large.